Proteoglycans and more – from molecules to biology - Heinegård, Dick (Blackwell Publishing Ltd, 2009)
In this article the organization and functional details of the extracellular matrix, with particular focus on cartilage, are described. All tissues contain a set of molecules that are arranged to contribute structural elements. Examples are fibril-forming collagens forming major fibrillar networks in most tissues. The assembly process is regulated by a number of proteins (thrombospondins, LRR-proteins, matrilins and other collagens) that can bind to the collagen molecule and in many cases remain bound to the formed fibre providing additional stability and enhancing networking to other structural networks. One such network is formed by collagen VI molecules assembled to beaded filaments in the matrix catalysed by interactions with small proteoglycans of the LRR-family, which remain bound to the filament providing for interactions via a linker of a matrilin to other matrix constituents like collagen fibres and the large proteoglycans, e.g. aggrecan in cartilage. Aggrecan is contributing an extreme anionic charge density to the extracellular matrix, which by osmotic effects leads to water retention and strive to swelling, resisted by the tensile properties of the collagen fibres. Aggrecan is bound via one end to hyaluronan, including such molecules retained at the cell surface, to form very large molecular entities that interact with other constituents of the matrix, e.g. fibulins that can form their own network. Other important interactions are those with cell surface receptors such as integrins, heparan sulphfate proteoglycans, hyaluronan receptors and others. Many of the molecules with an ability to interact with these receptors can also bind to molecules in the matrix and provide a bridge from the matrix to the cell and induce various responses. In pathology, there is an imbalance in matrix turnover with often excessive proteolytic breakdown. This results in the formation of protein fragments, where cleavage provides information on the active enzyme. Those fragments released can be specifically detected employing antibodies specific to the cleavage site and used to diagnose and monitor e.g. joint disease at early stages.